2018
DOI: 10.1039/c8nj02238k
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of planar heterojunction CsPbBr2I perovskite solar cells using ZnO as an electron transport layer and improved solar energy conversion efficiency

Abstract: Inorganic cesium lead bromoiodide based planar perovskite solar cells with ZnO electron transport layers are deposited using one step spin coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…[22,23] Moreover,t he extra high-density grain boundaries or long-chain surfactants used to improve processing of the materials lead to inferiorP CEs. [6,14,15,[24][25][26][27][28][29][30][31][32][33] An impressive PCE of 9.16 %w as achieved for carbon-based all-inorganic PSCs with pure CsPbIBr 2 in our previousw ork. [6,14,15,[24][25][26][27][28][29][30][31][32][33] An impressive PCE of 9.16 %w as achieved for carbon-based all-inorganic PSCs with pure CsPbIBr 2 in our previousw ork.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…[22,23] Moreover,t he extra high-density grain boundaries or long-chain surfactants used to improve processing of the materials lead to inferiorP CEs. [6,14,15,[24][25][26][27][28][29][30][31][32][33] An impressive PCE of 9.16 %w as achieved for carbon-based all-inorganic PSCs with pure CsPbIBr 2 in our previousw ork. [6,14,15,[24][25][26][27][28][29][30][31][32][33] An impressive PCE of 9.16 %w as achieved for carbon-based all-inorganic PSCs with pure CsPbIBr 2 in our previousw ork.…”
Section: Introductionmentioning
confidence: 59%
“…[22] On the other hand, CsPbIBr 2 has an arrower band gap ( % 2.05 eV) than CsPbBr 3 and better stabilityt han both CsPbI 3 and CsPbI 2 Br. [6,14,15,[24][25][26][27][28][29][30][31][32][33] An impressive PCE of 9.16 %w as achieved for carbon-based all-inorganic PSCs with pure CsPbIBr 2 in our previousw ork. [24] Doping CsPbIBr 2 with Mn 2 + or Sn 2 + was shown to further boost the cell efficiency to over 11 %.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Regarding the inorganic semiconductor materials, metal oxides possess superior stability and tunable optical and electrical properties compared with the organic semiconductor materials. The various metal oxides such as titanium dioxide (TiO 2 ), zinc oxide (ZnO), and tin oxide (SnO 2 ) are commonly used as the electron transport layer (ETL), while nickel oxide (NiO x ), copper oxide (Cu 2 O), copper (I) thiocyanate (CuSCN), copper gallium oxide (CuGaO 2 ), and nickel cobalt oxide (NiCoO x ) serve as the hole transport layer (HTL) in the PVSCs . Meanwhile, several theoretical studies based on different approaches to the device models have also been reported, focusing on the underlying physics of the efficiency loss, hysteresis phenomena, etc., which are substantially affected by the carrier transport layer (CTL) properties.…”
Section: Introductionmentioning
confidence: 99%